Inflammatory myofibroblastic tumor of the stomach in an adult female - report of a rare case and review of the literature - Ayushi JAIN,; Shweta KASANA,; Dilip RAMRAKHIANI,; Mukesh SHARMA, (Turkish Journal of Gastroenterology, 2019)
-